The public relations practices in high-tech organization Kulim high-tech park / Rozaidi Abdul Rahim Razali - Abdul Rahim Razali, Rozaidi (2011)
This thesis is about the practice of public relations in high-tech organizations of Kulim High-Tech Park. The research examines the model of communications, the roles and functions of public relations professionals in these organizations, their scope of participation in strategic decision making as well as the presence of Integrated Marketing Communications (IMC) and position of public relations in that mix. In this study, the researcher adopt a case study design to gain an in-depth understanding of the situation and meaning for those involved. This paper reports on a study using in depth interviews to better understand how public relations practices apply in high-tech organization. Research revealed that the organizations followed the asymmetric model of communication under a symmetric philosophy where participation in strategic decision making was marginal, with the role being mainly that of expert prescriber. In the IMC process, trend toward IMC has certainly entered Kulim High-Tech only the position of public relations in that set up is not clearly justified. IMC is mere technical function. Even though the idea of relating public relations roles in IMC exist but still some of the organizations are unaware of how public relations can complement the IMC process.